Bilateral radial agenesis with absent thumbs, complex heart defect, short stature, and facial dysmorphism in a patient with pure distal microduplication of 5q35.2-5q35.3 - Jamsheer Aleksander; Sowińska Anna; Simon Dorota; Jamsheer-Bratkowska Małgorzata; Trzeciak Tomasz; Latos-Bieleńska Anna (BMC, 2013)
Abstract Background A partial duplication of the distal long arm of chromosome 5 (5q35-- > qter) is known to be associated with a distinct phenotype referred to as Hunter-McAlpine syndrome. Clinical spectrum of this disorder mainly consists of mental retardation, microcephaly, short stature, skeletal anomalies, and craniofacial dysmorphism featuring flat facies, micrognathia, large, low-set dysplastic ears, hypertelorism, almond-shaped, down-slanted palpebral fissures, epicanthal folds, small nose, long philtrum, small mouth, and thin upper lip. Less frequent remarkable findings include craniosynostosis, heart defect, hypoplastic phalanges, preaxial polydactyly, hypospadias, cryptorchidism, and inguinal hernia. In most patients with a partial duplication of 5q the aberration occurred due to an inherited unbalanced translocation, therefore the phenotype was not reflective of pure trisomy 5q. Case presentation We report on a 9.5-year-old boy with some feature of Hunter-McAlpine syndrome including short stature, complex heart defect (dextrocardia, dextroversion, PFO), bilateral cryptorchidism, hypothyroidism, and craniofacial dysmorphism. Additionally, bilateral radial agenesis with complete absence of Ist digital rays, ulnar hypoplasia with bowing, choroidal and retinal coloboma, abnormal biliary vesicle were identified, which have never been noted in 5q trisomy patients. Karyotype analysis, sequencing and MLPA for TBX5 and SALL4 genes were unremarkable. Array comparative genomic hybridization detected a duplication on 5q35.2-5q35.3, resulting from a de novo chromosomal rearrangement. Our proband carried the smallest of all previously reported pure distal 5q trisomies encompassing terminal 5.4-5.6 Mb and presented with the most severe limb malformation attributed to the increased number of distal 5q copies. Conclusions We postulate that a terminal distal trisomy of 5q35.2-5q35.3, which maps 1.1 Mb telomeric to the MSX2 gene is causative for both radial agenesis and complex heart defect in our proband. A potential candidate gene causative for limb malformation in our proband could be FGFR4, which maps relatively in the closest position to the chromosomal breakage site (about 1.3 Mb) from all known 5q duplications. Since the limb malformation as well as the underlying genetic defect are distinct from other 5q trisomy patient we propose that a position effect resulting in altered long-range regulation of the FGFR4 (alternatively MSX2) may be responsible for the limb malformation in our proband.